Population structure and genetic stock identification in southeastern United States loggerhead sea turtles (Caretta caretta) using genome-wide SNPs - Ian Silver-Gorges; Lisa M. Komoroske; Jamie Adkins; John D. Swenson; David S. Addison; Derek A. Burkholder; Dean A. Bagley; Glenn D. Goodwin; Kristen M. Hart; Joseph B. Pfaller; Brian M. Shamblin; Mariana M. P. B. Fuentes (Conservation Genetics, 2026)
Characterizing the genetic structure and connectivity between populations of endangered species can be used to inform management actions. In vagile species with high gene flow or recently established populations, such characterizations can be difficult to undertake using traditional genetic markers, and genetic stock identification (GSI) may be confounded by allele-sharing between populations. Loggerhead sea turtles ( Caretta caretta ) in the southeastern United States comprise seven management units (MUs) based on female philopatry inferred via mitochondrial DNA sequences, yet nuclear microsatellite data do not reflect divergence. Further, loci for accurate GSI are not currently known. To address this, we generated genome-wide single nucleotide polymorphism (SNP) data from 146 females nesting at individual sites representative of each southeastern United States MU. We found weak (F ST =0.001–0.003) but significant divergence among all MUs, with more notable divergence between the Gulf Coast and Atlantic Ocean MUs, and amongst the Atlantic Ocean MUs. We then used an iterative leave-one-out approach to identify candidate loci for GSI. This approach identified loci that could assign individuals to natal ocean basins (i.e., to the Gulf Coast or to the Atlantic Ocean), and to individual MUs within the Atlantic Ocean, with high (≥90%) success and accuracy. Analyses of genome-wide SNPs refined our understanding of the magnitude and scale of population connectivity in loggerhead turtles in the southeastern United States, and provided a foundation for the development of SNP panels for accurate, fine-scale GSI in sea turtles.

A global assessment of microplastic abundance and characteristics on marine turtle nesting beaches - Zara L.R. Botterell; Jed Ardren; Elly Dove; Ellen McArthur; David S. Addison; Oyeronke M. Adegbile; Pierre Didier Agamboue; Andrews Agyekumhene; Phil Allman; Alexandra Alterman; Adren Anderson; Theresa Arenholz; et al. (Marine Pollution Bulletin, 2025)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Experimental quantification of mating disruption for false codling moth, Thaumatotibia leucotreta (Lepidoptera: Tortricidae), in stone fruit and table grape cultivation - Vernon M. Steyn; Antoinette P. Malan; Pia Addison (Crop Protection, 2024)

Participant Evaluation of a Multi-disciplinary Oncology Preceptorship Training Program for Oncology Health Professionals from Kumasi, Ghana - Kenneth W. Merrell; Thomas Okpoti Konney; Osei Acheamfour; Joseph Lucido; Abena Yeboah Aduse-Poku; Amanika Kumar; Mavis Bobie Ansah; Adu Tutu Amankwa; Dean Shumway; Fred Kwame Awittor; Augustina Badu-Peprah; Lionel Aurelien A. Kankeu Fonkoua; et al. (Journal of Cancer Education, 2024)
A critical shortage of skilled healthcare workers is a primary cause of disparate global cancer outcomes. We report participant evaluation of a multidisciplinary preceptorship program. In collaboration with the city of Kumasi, Ghana, Mayo Clinic and the City Cancer Challenge hosted a preceptorship program for comprehensive multidisciplinary breast and cervix cancer training. A total of 14 healthcare workers from Kumasi received two weeks of training at Mayo Clinic in November and December 2021. Each participant and preceptor were requested to complete an anonymous post-participation survey. Of the 14 trainee participants, 10 (71%) completed the survey. All respondents found the program “valuable and applicable to their clinical practice.” Ninety percent reported they were able to “review effective and critical elements in the development and expansion of the multidisciplinary team” and able to “solve practical clinical cases as a team”. General themes of satisfaction included: (1) organization and administration, (2) clinical observations and demonstrations, (3) guidelines development, and (4) recognizing the central importance of cultivating a team-based approach. Of the 40 preceptors, 16 (40%) completed the survey. All respondents reported they felt the training would meaningfully “influence patient care in Ghana”, that participation “added value or joy to their clinical practice,” and all wished to “participate in future preceptorship programs”. After a focused two-week program, trainees reported high satisfaction, usefulness from observing specialized cancer care, and value in closely observing a multidisciplinary oncology team. Preceptors reported the experience added joy and perspective to their clinical practice and wished to participate in future programs.

Monitoring population-level foraging distribution of a marine migratory species from land: strengths and weaknesses of the isotopic approach on the Northwest Atlantic loggerhead turtle aggregation - Simona A. Ceriani; Susan Murasko; David S. Addison; David Anderson; Greg Curry; Nicole A. Desjardin; Scott F. Eastman; Daniel R. Evans; Nancy Evou; Mariana M. P. B. Fuentes; Matthew H. Godfrey; Kristen M. Hart; et al. (Frontiers in Marine Science, 2023)
Assessing the linkage between breeding and non-breeding areas has important implications for understanding the fundamental biology of and conserving animal species. This is a challenging task for marine species, and in sea turtles a combination of stable isotope analysis (SIA) and satellite telemetry has been increasingly used. The Northwest Atlantic (NWA) loggerhead ( Caretta caretta ) Regional Management Unit, one of the largest sea turtle populations in the world, provides an excellent opportunity to investigate key biological patterns as well as methodological aspects related to the use of stable isotopes to infer spatial distribution of turtles in foraging areas. We provide the first comprehensive assessment of the annual distribution of NWA adult female loggerheads among foraging areas and investigate the efficacy of various analytical approaches as well as the effect of sample size in these types of studies. A total of 5168 individual females were sampled from seven Management Units (MUs) between 2013-2018. We provide the first estimate of the proportion of females originating from each MU that uses each foraging area and show how this proportion varies over time. We also estimate the relative importance (in terms of number of turtles) of each foraging area to the overall loggerhead breeding aggregation nesting in Florida and in the NWA for each year of the study. The foraging area used by reproductively active females differs considerably across MUs. One of these, the Subtropical NWA, is by far the most important foraging area in terms of both number of individuals and genetic diversity, and therefore this region may be considered as a conservation priority. Through simulations, we show that limited sizes of sample groups (unknowns; training; priors) may result in false geographic differentiation and consequently mislead interpretations. We provide thresholds and methodological recommendations for future studies. This study establishes a fundamental baseline for monitoring the annual contribution of foraging area to a terrestrial-based breeding aggregation of a marine animal in a cost-effective way. This type of monitoring allows for early detection of changes in foraging distributions—a possible effect of climate change on marine ecosystems or of area-specific anthropogenic threats.

Speciation with gene flow in a narrow endemic West Virginia cave salamander (Gyrinophilus subterraneus) - Evan H. Campbell Grant; Kevin P. Mulder; Adrianne B. Brand; Douglas B. Chambers; Addison H. Wynn; Grace Capshaw; Matthew L. Niemiller; John G. Phillips; Jeremy F. Jacobs; Shawn R. Kuchta; Rayna C. Bell (Conservation Genetics, 2022)

Competitive release during fire succession influences ecological turnover in a small mammal community - Addison G. Allen; Zachary P. Roehrs; R. Scott Seville; Hayley C. Lanier (Ecology, 2022)
Ecologists have long debated the relative importance of biotic interactions versus species‐specific habitat preferences in shaping patterns of ecological dominance. In western North America, cycles of fire disturbance are marked by transitions between North American deermice ( Peromyscus maniculatus ), which predominate after wildfires, and southern red‐backed voles ( Myodes gapperi ), which gradually replace deermice 3–4 years postfire and maintain dominance as forests mature. While this shift has been frequently documented, the processes that mediate this turnover are debated. One possibility is competitive release, which predicts a reduction in vole competition may contribute to niche expansion and population growth in deermice. Alternatively, turnover in both species may be shaped by differences in their preferred habitat and resource base, as predicted by optimum foraging theory. We evaluate these hypotheses using stable isotopes and spatial mark–recapture of deermouse and vole populations sampled prior to and following a fire as part of a longitudinal study in the Greater Yellowstone Ecosystem. Fire disturbance was associated with a 94% decrease in vole abundance but a 102% increase in deermice. Even after accounting for microhabitat, vole and deermouse populations were negatively correlated spatially and temporally ( R = −0.45), and competitor abundance was more important prefire than postfire. When vole abundance was high (prefire), vole dietary niche space was seven times broader than that of deermice. Postfire, deermouse dietary niche nearly tripled and was enriched in 13 C (i.e., more C 4 plants), while voles occupied a slightly reduced dietary niche (79% of prefire breadth). Our results suggest deermice are experiencing ecological release due to a reduction in vole competition but vole shifts are largely driven by habitat preferences.

From Science to Evidence – How Biodiversity Indicators Can Be Used for Effective Marine Conservation Policy and Management - Abigail McQuatters-Gollop; Ian Mitchell; Cristina Vina-Herbon; Jacob Bedford; Prue F. E. Addison; Christopher P. Lynam; P. N. Geetha; Estee Ann Vermeulan; Kaylee Smit; Daniel T. I. Bayley; Elisabeth Morris-Webb; Holly J. Niner; et al. (Frontiers in Marine Science, 2019)

Boundary spanning at the science–policy interface: the practitioners’ perspectives - A. T. Bednarek; C. Wyborn; C. Cvitanovic; R. Meyer; R. M. Colvin; P. F. E. Addison; S. L. Close; K. Curran; M. Farooque; E. Goldman; D. Hart; H. Mannix; et al. (Sustainability Science, 2018)

Effect of Dynamic Culture and Periodic Compression on Human Mesenchymal Stem Cell Proliferation and Chondrogenesis - Ting Guo; Li Yu; Casey G. Lim; Addison S. Goodley; Xuan Xiao; Jesse K. Placone; Kimberly M. Ferlin; Bao-Ngoc B. Nguyen; Adam H. Hsieh; John P. Fisher (Annals of Biomedical Engineering, 2016)

Investigating population differentiation in a major African agricultural pest: evidence from geometric morphometrics and connectivity suggests high invasion potential - M. Karsten; P. Addison; B. Jansen van Vuuren; J. S. Terblanche (Molecular Ecology, 2016)
The distribution, spatial pattern and population dynamics of a species can be influenced by differences in the environment across its range. Spatial variation in climatic conditions can cause local populations to undergo disruptive selection and ultimately result in local adaptation. However, local adaptation can be constrained by gene flow and may favour resident individuals over migrants—both are factors critical to the assessment of invasion potential. The Natal fruit fly ( Ceratitis rosa ) is a major agricultural pest in Africa with a history of island invasions, although its range is largely restricted to south east Africa. Across Africa, C. rosa is genetically structured into two clusters (R1 and R2), with these clusters occurring sympatrically in the north of South Africa. The spatial distribution of these genotypic clusters remains unexamined despite their importance for understanding the pest's invasion potential. Here, C. rosa , sampled from 22 South African locations, were genotyped at 11 polymorphic microsatellite loci and assessed morphologically using geometric morphometric wing shape analyses to investigate patterns of population structure and determine connectedness of pest‐occupied sites. Our results show little to no intraspecific (population) differentiation, high population connectivity, high effective population sizes and only one morphological type (R2) within South Africa. The absence of the R1 morphotype at sites where it was previously found may be a consequence of differences in thermal niches of the two morphotypes. Overall, our results suggest high invasion potential of this species, that area‐wide pest management should be undertaken on a country‐wide scale, and that border control is critical to preventing further invasions.

Within‐population heterogeneity of habitat use by lake trout Salvelinus namaycush - Y. E. Morbey; P. Addison; B. J. Shuter; K. Vascotto (Journal of Fish Biology, 2006)
To learn more about the degree of individual variation in resource use by lake trout Salvelinus namaycush , ultrasonic telemetry was used to study their habitat use in a lake without pelagic schooling fish prey. Individuals spent most of their time within the metalimnion in favourable water temperatures. They also made frequent excursions, however, into lake temperatures exceeding their optimum for physiological performance at all temporal scales considered. Their frequent use of nearshore habitats suggested that feeding in littoral areas may be common. Habitat use was highly variable among individuals, but spatial habitat use by individuals showed remarkable consistency between years. In particular, some lake trout exhibited high site fidelity to shallow, nearshore areas, whereas others used deep areas extensively. This level of between‐individual variation indicated niche partitioning by depth and the possibility of alternative foraging strategies.

CXC chemokines mechanism of action in regulating tumor angiogenesis - Bethany B. Moore; Douglas A. Arenberg; Christina L. Addison; Michael P. Keane; Peter J. Polverini; Robert M. Strieter (Angiogenesis, 1998)

Acoustic tracking of the dispersal of organic matter by scavenging fishes in the deep-sea - M. A. Collins; I. G. Priede; S. Addison; A. Smith; P. M. Bagley (Hydrobiologia, 1998)

Interception and dispersal of artificial food falls by scavenging fishes in the abyssal Northeast Atlantic: early-season observations prior to annual deposition of phytodetritus - A. Smith; I. G. Priede; P. M. Bagley; S. W. Addison (Marine Biology, 1997)

Systematic mass rearing and release ofMicroctonus hyperodae (Hym.: Braconidae, Euphorinae), a parasitoid of the argentine stem weevilListronotus bonariensis (Col.: Curculionidae) and records of its establishment in New Zealand - S. L. Goldson; M. R. McNeill; J. R. Proffitt; G. M. Barker; P. J. Addison; B. I. P. Barratt; C. M. Ferguson (BioControl, 1993)